2014
DOI: 10.5195/ijms.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Practices of Non-Pharmacological Approaches for Management of Hypertension in a Geriatric Population

Abstract: Background: There is an increase in the prevalence of hypertension all over the world, including India. Hypertension can be initially managed with non-pharmacological measures. This study aims to assess the knowledge of non-pharmacological measures to control hypertension and its application in a geriatric hypertensive population. Methods: The study was conducted at the Department of Physiology, SVU, Vadodara, India. A total 110 hypertensive patients were included in the study and a non-validated survey was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…On the other hand, this finding is similar to the study conducted in Bishoftu General Hospital, among the total respondents, 72.27% have good knowledge, 68.32% have a good attitude and 61.39% have good practice (17), This finding lower than the study conducted in Nekemte, 68.92% of the respondent had a good practice (7). good knowledge about healthy lifestyle (AOR:0.42; 95% CI: 0.24-0,74) (8), Of the total participants, only 25.2% (95% CI: 18.8-32.9) of the patients practised recommended lifestyle modifications, knowledge on hypertension management (AOR = 14.6, 95% CI: 4.6 - 45.9) (9), 87% of respondents measured their blood pressure regularly compared to 38% of the subjects did not measure their blood pressure regularly and 58.3 % did physical exercise compared to 88% of the study participants did not carry out any form of physical activity (18) Patients who had favorable attitude were 2.054 times more likely practice of NMM than who had unfavourable attitude (AOR: 2.052,95% CI: 1.180, 3.575), patients who had a family history of HTN were 1.764 times more likely practice of NMM than who hadn’t a family history of HTN (AOR: 1.764, 95% CI: 1.073, 2.899)…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this finding is similar to the study conducted in Bishoftu General Hospital, among the total respondents, 72.27% have good knowledge, 68.32% have a good attitude and 61.39% have good practice (17), This finding lower than the study conducted in Nekemte, 68.92% of the respondent had a good practice (7). good knowledge about healthy lifestyle (AOR:0.42; 95% CI: 0.24-0,74) (8), Of the total participants, only 25.2% (95% CI: 18.8-32.9) of the patients practised recommended lifestyle modifications, knowledge on hypertension management (AOR = 14.6, 95% CI: 4.6 - 45.9) (9), 87% of respondents measured their blood pressure regularly compared to 38% of the subjects did not measure their blood pressure regularly and 58.3 % did physical exercise compared to 88% of the study participants did not carry out any form of physical activity (18) Patients who had favorable attitude were 2.054 times more likely practice of NMM than who had unfavourable attitude (AOR: 2.052,95% CI: 1.180, 3.575), patients who had a family history of HTN were 1.764 times more likely practice of NMM than who hadn’t a family history of HTN (AOR: 1.764, 95% CI: 1.073, 2.899)…”
Section: Discussionmentioning
confidence: 99%
“…Hence, changes in lifestyle are needed, which can lead to a decrease in the use of pharmacological and invasive cardiovascular treatment approaches. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional and behavioral measures recommended in the management of high BP improved the patients’ general health status, as they also have a beneficial effect on other cardiac risk factors frequently associated with hypertension. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Small studies have shown that the majority of people living with hypertension do not know the normal BP levels and that correlation between body weight and elevated BP. 9 Hypertension is still a growing public health problem in Mexico. The National Health and Nutrition Survey (ENSANUT) reported prevalence figures for this condition of 25.5%, of which 40.0% were not aware they had it.…”
Section: Introductionmentioning
confidence: 99%